Analisis Peran Budaya Organizational Citizenship Behavior pada Peningkatan Kinerja Karyawan Lembaga Kursus dan Pelatihan Kampung Inggris Gunungpati Semarang - Alifia Putri Febriyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Kampung Inggris Semarang Training Institute (LKP Kampung Inggris Semarang), as a formal educational institution recognized by the Semarang City Department of Education, faces complex issues, including those related to employee performance. Organizational Citizenship Behavior (OCB) is expected to be one solution to these problems. This study aims to analyze the culture of Organizational Citizenship Behavior (OCB) among employees at LKP Kampung Inggris Semarang. The research uses a qualitative approach that is descriptive in nature with a case study method. Data collection techniques include observation, interviews, and document study. Data analysis techniques involve data reduction, data presentation, and conclusion drawing. The results of this study show that the Organizational Citizenship Behavior (OCB) of employees at LKP Kampung Inggris Semarang is built on five dimensions: altruism, conscientiousness, sportsmanship, courtesy, and civic virtue. The performance of employees at LKP Kampung Inggris Semarang meets five performance indicators: work quality, work speed/accuracy, work initiative, work ability, and communication. Organizational Citizenship Behavior (OCB) plays a role in improving employee performance, as reflected in the behaviors of employees at LKP Kampung Inggris Semarang. These five dimensions of OCB are shaped by internal factors (job satisfaction, organizational commitment, personality, morality, and motivation) and external factors (leadership style, trust in leadership, and organizational culture).